GENEALOGICAL RECONSTRUCTION IN THE HISTORIOGRAPHY OF TAFSIR: FROM CRITIQUE TO METHODOLOGICAL DEMONSTRATION - Syamsul Wathani; Machasin; Ahmad Baidowi (UIN Raden Mas Said Surakarta, 2026)
This article aims to discuss genealogy as an analytical tool and methodological framework for understanding the history of exegesis. This article poses two research questions: What are the key perspectives and ideas of the genealogical tradition in the study of the history of interpretation exegesis, and how does the genealogical tradition reconstruct the study of the history of exegesis. The analysis is conducted using the deconstructionist approach proposed by Jacques Derrida. This article presents several findings: First, genealogy conceptualizes the historical study of exegesis through the continuity of exegetical forms (genres) and the analysis of the historical configuration of Islam shaped by ideological, theological, discursive, and scholarly conventions; Second, genealogy encompasses five key concepts: the reliance on primary sources of exegesis, the recontextualization and adaptation of exegesis, exegetical quotations, exegetical summaries, and interpretive affinities; Third, these core concepts can function as methodological reconstruction tools in the historical study of exegesis through four analytical instruments: archaeological analysis, philological analysis, historical criticism, and ideological criticism. Genealogy provides an approach to the historical study of exegesis by emphasizing an integrative analysis that connects exegetical works with activities beyond them, allowing for an objective understanding of exegesis’s existence and a careful examination of how it produces meaning.